Ο περιβάλλοντας χώρος και ο ρόλος του στην εικονογράφηση του παιδικού παραμυθιού Χάνσελ και Γκρέτελ - Αντωνίου, Αναστασία (Department of Multimedia and Graphic Arts, Faculty of Fine and Applied Arts, Cyprus University of Technology, 2019)
The aim of the present study was to examine the methodology of the depiction as well as the physical environment of brothers Grimm, Hansel & Gretel fairy tale. To be precise the scenes of the gingerbread house belonging to the witch and the great forest. The purpose of the research was to inspect whether the representation of the setting, back in the 19th to the 21st century actually performed the function of fear creation for this specific fairy tale. The methodology utilized was content analysis where 107 different pictorial artifacts were analysed in regards to the colour, illustration techniques, the synthesis, seasons and even the time of the day, comparing between the day and night effect. Subsequently, the findings have been taken into account and presented through percentages via quantitative research methods, being interpreted as the objective findings of the research.
Keywords: Περιβάλλοντας χώρος; Σκηνικό; Παιδικό παραμύθι; Εικονογράφηση; Illustration; Setting; Picture books; Fairy-tale